Research on the Relationship Between Risk Management Mechanism and Corporate Governance Performance of Civil Aviation Enterprises - Zhang Yize (SHS Web of Conferences)
With the rapid development of the global civil aviation industry, the relationship between risk management mechanisms and corporate governance performance has received increasing attention. This study investigates the relationship between risk management mechanisms and the corporate governance performance of civil aviation enterprises. In this study, literature review and case analysis prove that effective risk management can help civil aviation enterprises reduce the impact of unforeseen risks, improve the quality of decision-making, and promote the improvement of corporate governance structure. Additionally, good corporate governance and performance benefit risk management and guide decision-making, giving implementation discipline for risk monitoring. The findings indicate that developing a scientific and systematic risk management system alongside an effective corporate governance structure is crucial for enhancing the core competitiveness of the civil aviation sector. This paper puts forward some management suggestions to assist civil aviation in optimizing the existing risk management mechanism and corporate governance model and address the problems in increasingly complex and changeable market environments.